دراسة وصفية للمخطوط شمس الضحى في شرح مصباح الدجى: A Descriptive Study of the manuscript Shams ul-Duha fi Sharh e Misbah el-Duja - Akram Nizami, Dr. Muhammad; Nasrullah, Dr. Sadia (Al-Amīr Research Journal for Islamic Studies, 2023)
Sheikh Ghulam Al-Murtada(1835) is one of the most prominent Pakistani scholars before partition. He was well-versed in the sciences of the Arabic language and its literature, including grammar, morphology, and the various Arabic dialects. He was a good scholar in the sciences prevalent in his time, such as Tafseer, Hadith, Islamic jurisprudence, history, and the Seerat-un-Nabi ﷺ. He educated people with these Islamic and Arabic literary disciplines in the distant outskirts of the River Jhelum in the village of Beerbal. He established educational institution and wrote a number of valuable books. It is not appropriate for us to forget the author’s commendable efforts and endeavors. His book Shams ul Duha was a hidden pearl until now. It is our duty to unveil his significant work and bring it to light, So that the world can know about his great achievements. Therefore, this descriptive study has been done to contribute to preserving this large, abundant knowledgeable treasury. The manuscript “Shams ul-Duha fi Sharh e Misbah el-Duja” is proof of the Arabic and literary heritage of indian sub continet and it is a unique effort This artical will mention its value, and its great importance. It will not only serve the Arabic language and its literature, but will give a new direction to readers and researchers in this regard. Key Words: Sub-Continent, Manuscript, Hadith science, Heritage Revival, Shams ul-Duha, Ghulam ul Murtaza